Correlation between Junior High School Students’ Self-Efficacy in Writing and Their Writing Performance - Dian Aushaf Yasmin; Rahayu Kuswardani (Retain: Journal of Research in English Language Teaching, 2025)
This study’s purpose is to find out the writing self-efficacy level of eighth-grade students in a public junior high school in Surabaya and the correlation between students’ self-efficacy in writing and their writing performance. The data is gathered by using a questionnaire to measure the self-efficacy level and students’ latest writing assignment to measure their writing performance. This study used Pearson’s correlation method at first, but since the data distribution was considered abnormal, Spearman’s correlation method was chosen instead. The results of this research denote that the eighth-graders in this junior high school have a high level of self-efficacy in writing, with their average score being 3.56 out of 5. Students can perform well in writing, as can be seen from their writing assignment’s drafts. The Spearman’s correlation result for the students’ writing self-efficacy and writing performance, with the correlation coefficient being 0.264, barely confirms the theory that there is a positive and linear correlation between the two variables, in which most students who have high self-efficacy level are proved to perform their writing assignment well. As the two variables can affect each other, increasing students’ self-efficacy in writing can be one of the ways to improve the students’ writing performance, which will also increase the students’ motivation and confidence. Since this study is only conducted in one junior high school in Surabaya, it can’t perfectly represent the other schools, especially the schools in smaller cities. Future researchers may investigate the connection and relationship between students' writing performance and their writing self-efficacy, not only in junior high school but also at other educational levels, as well as using different types of text to further prove the theory of self-efficacy to see if self-efficacy impacts performance differently across various writing genres.